The Media: Ethical, Linguistic and Perlocutionary Parameters of Social Anti-Drug Advertising (Proceedings of Southern Federal University. Philology, 2018)
Lyudmila A. Brusenskaya, Ella G. Kulikova (Rostov-on-Don, Russian Federation)Various speech genres presuppose not only general, but also special genre norms. In recent works, social advertising is treated as a special speech genre. Social advertising, which refers to the ethical categories have become especially popular because the society arose such problem, the solution of which depends on the public behavior. Social advertising is often seen as a kind of counterweight to commercial PR and commercial advertising. Advertising is impossible without creativity – creativity focused on pragmatics. Creative social advertising is not confined within the strict literary norm. Social advertising, to impact and attract attention, should correlate with the parameters of the rest of the media.Anti-drug messages should be targeted. And in all cases, anti-drug advertising text, with bright visuals is able to form anti-drug installation on subconscious level. Anti-drug advertising should not include names of specific drugs, mention of method of manufacture or use, there should be no images of drug use. To best achieve its objectives, an advertisement must be provided by scientific support. We need a scientific evaluation of the success of advertising measures. Effectiveness of commercial advertising may find itself quickly enough, while the perlocutionary effect of social advertising is delayed in time. It is important to analyze the situation before advertising and after the intervention.Key words: anti-drug social advertising, ethic and linguistic norms, persuasion, perlocutive effect.DOI 10.23683/1995-0640-2018-1-142-150